Kandungan Logam Berat Pb, Cu dan Zn pada Siput Hitam (Faunus ater) dari Perairan Muara Sungai Air Bangis Sumatera Barat - Maulani, Atia; Amin, Bintal; ', Thamrin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Analysis of lead, copper and zinc in black snail (Faunus ater) in Air Bangis estuary was conducted in August 2014 with the aim to determine the pollution level in the estuary as well as to evaluate the safety of the snail for human consumption. The result showed that the average concentration of lead was 7.91 μg/g, copper 10.58 μg/g and zinc 65.11 μg/g. Higher metal concentration was found in the muscle body and smaller size of tha snail accumulated higher concentration of the metals studied. The MPI value of 75.28 in the estuary is categorize as can be tolerated by aquatic organisms. PTWI calculation for lead (0.88 kg/week), copper (92.8 kg/week) and zinc (30.09 kg/week) indicated that the snail from Air Bangis estuary is still considered to be safe for human consumption.Keywords: Heavy Metal, Faunus ater, Pollution, West Sumatra.